Correlates and characteristics of hepatitis C virus‐specific T‐cell immunity in exposed uninfected high‐risk prison inmates. Issue 4 (15th October 2012) - Cameron, B.; Galbraith, S.; Li, H.; Lloyd, A.; ,
Summary Some hepatitis C (HCV)‐uninfected, high‐risk individuals have HCV‐specific cellular immunity without viraemia or seroconversion. The characteristics of these responses and the risk behavioural associations were studied in 94 subjects in a prospective cohort of recently seronegative prisoners reporting injecting drug use (IDU). Detailed behavioural data were collected. HCV antibody and PCR testing were performed. ELISpot assays for HCV‐induced interferon (IFN)‐γ and interleukin (IL)‐2 production by T lymphocytes, as well as multiplex in vitro cytokine production assays, were performed. Seventy‐eight subjects remained antibody and PCR negative and 16 seroconverted. Of the seronegative group, 22 (28%) had IFN‐γ ELISpot responses in comparison with 13 of the 16 seroconverters (82%). This seronegative immune status was associated positively with injecting anabolic steroids and negatively with a recent break from IDU. The IFN‐γ ELISpot responses involved both CD4 and CD8 T lymphocytes and were comparable in magnitude, but narrower in specificity, in uninfected subjects than in seroconverters. A subset of seronegative subjects had HCV‐induced cytokine production patterns comparable with the seroconverters with increased production of IFN‐γ, IL‐2 and tumour necrosis factor (TNF)‐α and reduced IL‐10 in response to nonstructural peptides. In conclusion, comparable patterns of HCV‐specific cellular immunity are found in recently infected subjects and in a minority of high‐risk, uninfected subjects. Further characterization of these responses and their protective efficacy will inform HCV vaccine development.